Review papersFarmers’ occupational diseases of allergenic and zoonotic origin - Żukiewicz-Sobczak, Wioletta A.; Chmielewska-Badora, Jolanta; Wróblewska, Paula; Zwoliński, Jacek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Farmers are exposed to a number of biological, physical and chemical factors harmful to the health, resulting from the specific nature of their work environment. As is clear from epidemiological studies about occupational diseases, pneumoconioses and infectious and parasitic diseases are recorded most commonly. Due to the character of farmer’s work, the greatest risk to his health is biological hazards in the form of numerous microorganisms and their metabolites, and particles of plants and animals contained in the organic dust and pathogens transmitted by vectors such as ticks. The health status of farmers is often worse than of other professional groups as a result of limited access to health care and lower health literacy. Therefore, farmers should be subject to a system of diagnosing occupational diseases, and many preventive and educational programs concerning health risks associated with their work. The aim of this paper is to characterize occupational diseases of farmers including allergic diseases, tick-borne diseases and zoonoses.